High‐throughput single‐molecule studies of protein–DNA interactions. Issue 19 (21st May 2014) - Robison, Aaron D.; Finkelstein, Ilya J.
Abstract : Fluorescence and force‐based single‐molecule studies of protein–nucleic acid interactions continue to shed critical insights into many aspects of DNA and RNA processing. As single‐molecule assays are inherently low‐throughput, obtaining statistically relevant datasets remains a major challenge. Additionally, most fluorescence‐based single‐molecule particle‐tracking assays are limited to observing fluorescent proteins that are in the low‐nanomolar range, as spurious background signals predominate at higher fluorophore concentrations. These technical limitations have traditionally limited the types of questions that could be addressed via single‐molecule methods. In this review, we describe new approaches for high‐throughput and high‐concentration single‐molecule biochemical studies. We conclude with a discussion of outstanding challenges for the single‐molecule biologist and how these challenges can be tackled to further approach the biochemical complexity of the cell.